The Profiles of Hepatitis B and C Virus Infections in Prison-Assisted Citizens - Patricia Gita Naully (Biomedika, 2020)
Prison-assisted citizens or prisoners are one of the groups of people who are at high risk of Hepatitis B and C virus infections. The data on the prevalence of both viruses in prisoners in Indonesia are still limited. This study aims to determine the profiles of Hepatitis B and C virus infections in prison-assisted citizens in the Class IIA Narcotics Correctional Institution in Bandung Regency. A total of 30 prisoners were used as the samples in this study. All procedures performed in this study were following the applicable codes of ethics. The presence of surface antigens of Hepatitis B virus (HBsAg) in serums was detected using a qualitative sandwich Enzyme-Linked Immunosorbent Assay method. The existence of antibodies of the Hepatitis C virus (Anti-VHC) was detected using the immunochromatography method. The laboratory test results have shown five people (16.7%) were positive on the HBsAg test and one person (3.3%) was positive on the anti-VHC test. One case of Hepatitis B and C co-infection was also found in the prison-assisted citizens who were in the Class IIA Narcotics Correctional Institution in Bandung Regency. All the prisoners infected by the Hepatitis B and C viruses used injection drugs, had tattoos on their bodies and never received vaccinations.